Hydrophilic/hydrophobic surface modification impact on colloid lithography: Schottky-like defects, dislocation, and ideal distribution; Applied Surface Science; Vol. 433 - Burtsev V. Vasilii; Marchuk V. Valentina; Kugaevskiy A. Artem; Guselnikova O. A. Olga Andreevna; Elashnikov R. Roman; Milyutina (Miliutina) E. V. Elena Vadimovna; Postnikov P. S. Pavel Sergeevich; Svorcik V. Vaclav; Lyutakov O. Oleksy (2018, 2018)
Title screen